Oh What a Circus, oh what a Show. Puppets in the Circus and the Circus with Puppets - Janus, Maria (Not just the Clown and the Tiger. Sketches about Circus Arts, 2019)
Puppetry art it is not only a puppet theatre, but also a puppet cabaret, a variété and a puppet circus. The text presents puppet circus performances and circus-inspired puppet theatre shows. It searches for the puppet-inspired elements in nouveau cirque. Moreover, the article also discusses performances made by sculptor Alexander Calder which combine circus inspirations and animated objects. The author tries to explain reasons for preparing puppet circus performances and the use of circus inspirations and aesthetics in theatre performances.